2009
DOI: 10.1186/1471-2164-10-336
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genomics approach to understanding the biosynthesis of the sunscreen scytonemin in cyanobacteria

Abstract: Background: The extracellular sunscreen scytonemin is the most common and widespread indolealkaloid among cyanobacteria. Previous research using the cyanobacterium Nostoc punctiforme ATCC 29133 revealed a unique 18-gene cluster (NpR1276 to NpR1259 in the N. punctiforme genome) involved in the biosynthesis of scytonemin. We provide further genomic characterization of these genes in N. punctiforme and extend it to homologous regions in other cyanobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 39 publications
(55 reference statements)
3
85
0
Order By: Relevance
“…The products of NpR1263 and NpR1269 ORFs are still to be functionally characterized. From a comparative study of four other cyanobacterial strains, Soule et al [201] suggested that two supplementary conserved clusters (NpF5232 to NpF5236) and a putative two-component regulatory system (NpF1277 and NpF1278) are possibly involved in scytonemin biosynthesis and regulation, respectively, on the basis of conservation and location.…”
Section: Biosynthesis Of Scytoneminmentioning
confidence: 98%
See 2 more Smart Citations
“…The products of NpR1263 and NpR1269 ORFs are still to be functionally characterized. From a comparative study of four other cyanobacterial strains, Soule et al [201] suggested that two supplementary conserved clusters (NpF5232 to NpF5236) and a putative two-component regulatory system (NpF1277 and NpF1278) are possibly involved in scytonemin biosynthesis and regulation, respectively, on the basis of conservation and location.…”
Section: Biosynthesis Of Scytoneminmentioning
confidence: 98%
“…All 18 genes are co-transcribed as a single transcriptional unit that is upregulated by UV radiation [200]. Based on genetic, biochemical and sequence similarity evidence, Soule et al [201] illustrated that six putative genes in the scytonemin gene cluster (NpR1276 to NpR1271) with no previously known protein functions are likely involved in the assembly of scytonemin from central metabolites. The assessment of these gene clusters disclosed the occurrence of redundant copies of genes responsible for aromatic amino acid biosynthesis.…”
Section: Biosynthesis Of Scytoneminmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the remaining genes is a putative glycosyltransferase encoded by Npun_R1270. The specific function of this glycosyltransferase is unknown, although its location within the scytonemin gene cluster suggests that it may play a role in exporting the pigment to the extracellular sheath [33]. Moreover, glycosyltransferases have been shown to be involved with EPS biosynthesis [26,36].…”
Section: Introductionmentioning
confidence: 99%
“…However, the products of NpR1263 and NpR1269 ORFs are still to be functionally characterized. Soule et al (2009b) suggested that two additional conserved clusters, NpF5232 to NpF5236 and a putative two-component regulatory system (NpF1277 and NpF1278), are likely involved in scytonemin biosynthesis and regulation, respectively, on the basis of conservation and location.…”
Section: Structure and Biosynthesis Of Scytoneminmentioning
confidence: 99%